Is AI Accurate for Skin Cancer Detection? A Reality Check on Deep Learning in Dermatology - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The integration of Artificial Intelligence AI in medicine, particularly in diagnostics, has sparked both excitement and scrutiny. Few areas have seen as much...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care